Analysis of Accountability and Transparency in The Management of Fund Allocation in Panggung Village and Panggung Baru Village, Pelaihari District - seprina riani; Ines Saraswati Machfiroh; Fitra Izzadienny; Machfiroh, Nor Rahma Rizka (Universitas Cenderawasih, 2025)
Analysis was carried out on the management of Village Fund Allocation (ADD) in Panggung Village and Panggung Baru Village, Pelaihari District. This research is based on differences in the implementation of accountability and transparency in the two villages, as well as cases of irregularities in village financial management in Panggung Baru Village in the previous year's budget. The aim of the research is to spread accountability and transparency based on Minister of Home Affairs Regulation Number 20 of 2018. The method used is descriptive qualitative with data collection techniques through interviews, documentation and observation. Panggung Village shows fairly good implementation of accountability and transparency, but is still lacking in providing open information. Panggung Baru Village has used the Siskeudes application, but transparency is not optimal because social media is not active and there are no financial information billboards. Both villages need to increase information disclosure and community participation in ADD management.